2005
DOI: 10.1111/j.0735-2166.2005.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Metropolitan Latino Political Behavior: Voter Turnout and Candidate Preference in Los Angeles

Abstract: Most research on Latino voting behavior conclusively finds that as a group, Latinos vote at lower rates than other racial and ethnic groups in the United States. In this article, we argue that given the appropriate circumstances, Latinos should be expected to vote at higher rates than other racial and ethnic groups. In particular, we think the presence of a viable Latino candidate will spur increased Latino turnout and that when Latinos candidates run for office, Latino voters will prefer the co-ethnic candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 30 publications
3
55
0
Order By: Relevance
“…Although previous research examined the effect of one Latino candidate in isolation, either for a single congressional district (Cain and Kiewiet 1984), statewide office but limited to one state (Graves and Lee 2000), or for mayoral candidates, but in just one city (Barreto, Villarreal, and Woods 2005;Hill, Moreno, and Cue 2001;Manzano and Vega 2006), this study is the first to bring together multiple data sets from across the country to test the systematic effect of Latino candidates on political participation. To some degree, previous analysis is limited to the extent that the factors present in one city or state may not be present in other areas throughout the nation.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous research examined the effect of one Latino candidate in isolation, either for a single congressional district (Cain and Kiewiet 1984), statewide office but limited to one state (Graves and Lee 2000), or for mayoral candidates, but in just one city (Barreto, Villarreal, and Woods 2005;Hill, Moreno, and Cue 2001;Manzano and Vega 2006), this study is the first to bring together multiple data sets from across the country to test the systematic effect of Latino candidates on political participation. To some degree, previous analysis is limited to the extent that the factors present in one city or state may not be present in other areas throughout the nation.…”
Section: Resultsmentioning
confidence: 99%
“…Latinos, when stimulated by sense of commonality and ethnic group consciousness, are more likely to participate in a wide range of political activities, including voting (Stokes, 2003). The presence of a coethnic candidate has also been found to be a mobilizing force for Latinos (Barreto & Masuoka, 2004;Barreto, Villarreal, & Woods, 2005). Yet, despite the increase in research on Latino political behavior, significantly less attention has been devoted to the issue of vote choice.…”
mentioning
confidence: 99%
“…However, these differences appear to be, if anything, diminishing over time and generations, but an ethnic dimension to behaviours is still evident. For example, Barreto et al (2005), whose quantitative findings indicated that the presence of a Hispanic candidate in an election boosts turnout among Hispanic voters and support for that co-ethnic candidate, cited the anecdotal examples of Houston, where a Cuban-born, registered Republican candidate received over 70% of the Hispanic vote, mainly Mexican Americans who normally vote for Democratic candidates, and Miami, where a second-generation Cuban American, a registered Democrat, received over 70% of the vote from Hispanic voters who are largely Republican identifiers. 24 As noted, immigration and language are key issues.…”
Section: Hispanic Americansmentioning
confidence: 99%